Screening Older Adult Men for Abdominal Aortic Aneurysm: A Scoping Review. Issue 2 (March 2021) - Bains, Priya; Oliffe, John L.; Mackay, Martha H.; Kelly, Mary T.
Abdominal aortic aneurysm (AAA) is a potentially fatal condition predominantly affecting older adult men (60 years or over). Based on evidence, preventative health-care guidelines recommend screening older males for AAA using ultrasound. In attempts to reduce AAA mortality among men, screening has been utilized for early detection in some Western countries including the UK and Sweden. The current scoping review includes 19 empirical studies focusing on AAA screening in men. The findings from these studies highlight benefits and potential harms of male AAA screening. The benefits of AAA screening for men include decreased incidence of AAA rupture, decreased AAA mortality, increased effectiveness of elective AAA repair surgery, and cost-effectiveness. The potential harms of AAA screening included lack of AAA mortality reduction, negative impacts on quality of life, and inconsistent screening eligibility criteria being applied by primary care practitioners. The current scoping review findings are discussed to suggest changes to AAA screening guidelines and improve policy and practice.